2005
DOI: 10.1007/s10495-005-2946-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced apoptosis in endothelial cells and embryonic stem cells

Abstract: Hypoxia increases both HUVEC and mouse EB apoptosis, which is associated with increase in p53/Bax expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Under hypoxic conditions survival and proliferation of the cells were impaired, while in a normoxic atmosphere cell damage was even more severe. For glucose/serum starved HUVECs, hypoxia apparently acts as protective factor, while other groups described deleterious effects of hypoxia on HUVECs and mature endothelial cells kept in normal medium [15,16,17]. The damage to glucose/serum starved HUVECs was alleviated by CBMSC-conditioned medium, which reduced apoptotic and necrotic cell death and increased the number of metabolically active cells with preserved proliferative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Under hypoxic conditions survival and proliferation of the cells were impaired, while in a normoxic atmosphere cell damage was even more severe. For glucose/serum starved HUVECs, hypoxia apparently acts as protective factor, while other groups described deleterious effects of hypoxia on HUVECs and mature endothelial cells kept in normal medium [15,16,17]. The damage to glucose/serum starved HUVECs was alleviated by CBMSC-conditioned medium, which reduced apoptotic and necrotic cell death and increased the number of metabolically active cells with preserved proliferative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the predilection site of eroded plaques in humans has not been well elucidated until now. It has been also reported that hypoxia, oxLDL, homocysteine, oxygen-derived free radicals and some cytokines in blood can induce endothelial cell apoptosis (Isner et al 1995;Konno et al 1999;Mercie et al 2000;Lee et al 2005). Some researchers also demonstrated that apoptosis-induced genes like Bax, Fas and p53 were upregulated in atherosclerotic plaques (Kockx 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The p53 tumor suppressor is a ubiquitously-expressed transcription factor that is activated by DNA damage (D'Sa-Eipper et al, 2001;Katayama et al, 2002) and other cellular stressors, such as hypoxia (Long et al, 1997;Lee et al, 2005). The primary function of this protein is to induce cells to undergo G 1 arrest (Xiong et al, 1993;elDeiry et al, 1994) or apoptosis by activating the appropriate target genes.…”
Section: Genetic Models Of Cell Death In Mouse Placentamentioning
confidence: 99%